Domestic Value Added in Exports : Theory and Firm Evidence from China - Kee, Hiau Looi; Tang, Heiwai (World Bank, Washington, DC, 2015)
China has defied the declining trend in domestic content in exports in many countries. This paper studies China’s rising domestic content in exports using firm- and customs transaction-level data. The approach embraces firm heterogeneity and hence reduces aggregation bias. The study finds that the substitution of domestic for imported materials by individual processing exporters caused China’s domestic content in exports to increase from 65 to 70 percent in 2000–2007. Such substitution was induced by the country’s trade and investment liberalization, which deepened its engagement in global value chains and led to a greater variety of domestic materials becoming available at lower prices.